Effect of Levodopa on Speech Dysfluency in Parkinson's Disease. Issue 2 (30th December 2018) - Im, Hannah; Adams, Scott; Abeyesekera, Anita; Pieterman, Marcus; Gilmore, Greydon; Jog, Mandar
ABSTRACT: Objective: To examine the effect of levodopa medication on speech dysfluency in Parkinson's disease. Methods: Fifty‐one individuals with Parkinson's disease (IWPD) read aloud during off‐ and on‐ medication states. Total speech dysfluencies were calculated from transcriptions of recorded speech samples. Results: Severity of speech dysfluency was not significantly related to the severity of motor symptoms, duration of disease, levodopa equivalent dosage, or age. When the IWPD were divided into two groups based on dysfluency severity, there was a significant group‐by‐medication state interaction. There was a significant correlation between the medication‐related change in speech dysfluency and the off ‐medication severity of speech dysfluency measure (r = −0.46). Conclusions: The results of this study indicate that levodopa medication can have a significant effect on speech dysfluency. The beneficial levodopa effect appears to be related to the severity of the off‐ medication speech dysfluency. Results did not provide strong support for the excess dopamine theory of stuttering in IWPD. A dualistic model of the effects of dopamine on speech fluency in PD is proposed.